Fruit and vegetables consumption among school-going adolescents: Findings from the baseline survey of an intervention program in a semi-urban area of Dhaka, Bangladesh. - Marium Salwa (Public Library of Science (PLoS), 2021)
Introduction Interventions aimed at promoting healthy eating habits in adolescence can help prevent chronic diseases and promote healthy ageing. The aim of this paper is to describe the fruit and vegetables consumption habits of adolescents in Dhaka, Bangladesh as well as to identify the socio-environmental, personal, and behavioral factors that influence these habits. Materials and methods The baseline data from an intervention study involving 823 grade ten students from two randomly selected secondary schools in a semi-urban area of Dhaka were analyzed. The intake of fruit and vegetables was measured in terms of serving size per day. Hierarchical multiple regression was used to assess the ability of socio-environmental factors such as social support, perceived barriers, and living with patient with chronic diseases; personal factors such as knowledge, self-rated practice, behavioral intention, and body mass index; and behavioral factors such as physical activity, sedentary hours, and sleep duration to predict the level of daily fruit and vegetables intake, after controlling the effect of demographic characteristics of adolescents. Results The average daily consumption of fruit and vegetables was 1.22 and 1.99 servings, respectively. Only one-fifth of the respondents (21%) reported eating five servings of fruit and vegetables a day. Inaccessibility at home was reported as the most perceived barrier for both fruit and vegetables intake. Adolescents' higher fruit and vegetables intake was found to be associated with higher maternal educational attainment, more social support, adequate self-rated practice, positive behavioral intention, higher body mass index, better physical activity, and adequate daily sleeping. Conclusion The findings revealed insufficient fruit and vegetables intake among adolescents in a semi-urban area of Bangladesh and associated socio-environmental, personal, and behavioral factors that were utilized in developing an intervention program for this transient age group. Trial registration Trial was registered at ClinicalTrials.gov (NCT03975335) https://clinicaltrials.gov/ct2/show/NCT03975335 on June 01, 2019.